Characterization and mechanical properties of calcium silicate/citric acid-based polymer composite materials - Shirazi, F.S.; Mehrali, M.; Oshkour, A.A.; Metselaar, H.S.C.; Kadri, Nahrizul Adib; Abu Osman, Noor Azuan (Wiley, 2015)
Optimal implants for bone tissue engineering require sufficient mechanical strength as well as apt bioactivity and biodegradability. Calcium silicate (CaSiO3 - CS) ceramics have been studied for tissue engineering and implantation for their good bioactivity properties. Elastomer poly (1.8-octanediol citrate) (POC), one of the most biocompatible polymer, is used for biomedical application. The objective of this study is to fabricate a novel composite of calcium silicate with different ratios of POC to enhance the mechanical properties. The results showed that the compressive and the bending strengths of calcium silicate/POC biocomposite were improved remarkably at 40 wt POC.